Self-determined stories: the Indigenous reinvention of young adult literature - Suhr-Sytsma, Mandy (American Indian studies series., 2019)
"As the first book-length study of Indigenous-authored Young Adult literature, this project advances conversations in Native Studies about the meaning of Indigenous sovereignty and expands conceptualizations of power dynamics and genre in YA Literary Studies"--Provided by publisher.